Pengaruh Rendam Kaki Menggunakan Air Hangat Dengan Larutan Garam Untuk Mengurangi Derajat Oedema Pada Pasien Gagal Ginjal Kronik Di Murni Teguh Memorial Hospital - Dezza Junnyka Watubella; Mhd. Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Chronic Kidney Disease (CKD) is a condition in which the kidneys have experienced damage or functional or structural disorders. The condition of the kidneys experiencing decreased function and being unable to remove waste products through urine can result in disruption of endocrine, fluid, electrolyte, metabolic and acid-base functions, one of the consequences of which is the occurrence of edema. One of the non-pharmacological treatments for chronic kidney failure is warm water foot soak therapy with salt solution at a temperature of 38°c. Objective: This study aims to determine the effect of soaking feet using warm water and salt solution to reduce the degree of edema in patients with chronic kidney failure. Method: This research uses quantitative methods with a quasi-experimental research design with a pre-test post-test control group approach. Sampling used the Purposive Sampling technique with the Roscoe method. The number of respondents was 40 respondents (Intervention and Control). This research instrument used a pitting edema scale, sphygmomanometer and observation sheet. Results: This study used the Wilcoxon test and the Mann Whitney test. Conclusion: There is an effect of soaking feet using warm water with a salt solution to reduce the degree of edema in chronic kidney failure patients with a P-value of 0.016. It is recommended to carry out further research with more samples and adding variables.